Positive active material for lithium secondary battery and manufacturing method thereof
By using layered metal oxide structure and high nickel-based materials in the positive electrode active material of lithium secondary batteries, combined with specific lithium and metal replacement amounts and sintering conditions, the stability and capacity reduction of positive electrode active material in the prior art is solved. The problem of this achieves high energy density and long-life battery performance.
Patent Information
- Application Number
- CN202380048882.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-21
- Filing Date
- 2023-06-21
- Publication Date
- 2025-02-11
AI Technical Summary
The positive electrode active substances of existing lithium secondary batteries have problems of stability and capacity reduction during the synthesis process. Especially due to the instability of Ni(III), it is difficult to synthesize stoichiometric materials. Slight changes in lithium content lead to significant changes in electrochemical properties. .
Using a layered metal oxide crystal structure of the lithium layer and the metal layer, a high nickel-based positive electrode active material was prepared by controlling the replacement amount of lithium and metal, with a nickel content of more than 80 mol% and a replacement amount of lithium of more than 1.5 mol% and more than 1.5 mol%. Synthesis is carried out by a specific firing temperature and the molar ratio of the lithium raw material.
The positive electrode active substance of lithium secondary battery with high price competitiveness, high stability, high energy density, high capacity and high lifespan are achieved, ensuring the structural stability and electrochemical performance of the battery during charging and discharging.
Smart Images

Figure CN119422260A_ABST
Abstract
Description
Technical Field
[0001] According to one embodiment of the present invention, a positive active material for a lithium secondary battery and a method for manufacturing the same are provided. Background Art
[0002] Recently, due to the expansion of demand for electric vehicles, the demand for lithium secondary batteries that drive electric vehicles is growing rapidly. Layered lithium transition metal oxides (LiMO2, M = Ni, Co, Mn, etc.) are mainly used as positive electrode active materials for these lithium secondary batteries, and research to increase capacity is being actively conducted. Among the existing layered positive electrode active materials, LiNiO2 and high-nickel layered positive electrode materials have the highest capacity, but due to the instability of Ni (III), it is difficult to synthesize stoichiometric materials, and even if the lithium content changes slightly during the synthesis process, the electrochemical performance will change significantly. Summary of the invention
[0003] Technical issues
[0004] According to one embodiment of the present invention, a high-nickel-based positive electrode active material with excess lithium having high price competitiveness, high stability and high energy density and a method for manufacturing the same are provided.
[0005] Technical Solution
[0006] According to one embodiment of the present invention, a positive electrode active material is provided. The positive electrode active material comprises a layered metal oxide crystal structure of a lithium layer and a metal layer, wherein the crystal structure comprises a first metal layer, wherein a portion of the metal in the metal layer is replaced by lithium, wherein the crystal structure comprises a first lithium layer, wherein a portion of the lithium in the lithium layer is replaced by metal, wherein the amount of lithium replaced in the first metal layer is 1.5 mol% or more, and the content of nickel is 80 mol% or more, based on the metal content in the positive electrode active material being 100 mol%.
[0007] The replacement amount of lithium in the first metal layer is 1.5 mol % to 15 mol %.
[0008] The replacement amount of the metal in the first lithium layer is 0.5 mol % to 5 mol %.
[0009] The amount of lithium substituted in the first metal layer is greater than the amount of metal substituted in the first lithium layer.
[0010] The replacement amount of lithium in the first metal layer differs from the replacement amount of metal in the first lithium layer by 1 mol % to 15 mol %.
[0011] The molar ratio of all metals in the positive electrode active material to lithium is 1.01 to 1.2.
[0012] When the positive electrode active material is charged and discharged in the range of 2.5V to 4.25V, the c-axis lattice constant change rate of the R-3m structure is 2.5% or less.
[0013] When the positive electrode active material is charged and discharged in the range of 2.5V to 4.25V, the maximum value of the c-axis lattice constant of the R-3m structure is the following.
[0014] When the positive electrode active material is charged and discharged in the range of 2.5V to 4.25V, the c-axis lattice constant of the R-3m structure is to range changes.
[0015] The bond length between the metal and oxygen in the positive electrode active material is the following.
[0016] The content of Li2CO3 present in the positive electrode active material is less than 0.5 wt % as measured by X-ray diffraction analysis.
[0017] The content of Li2O present in the positive electrode active material is less than 1.0 wt% as measured by X-ray diffraction analysis.
[0018] The content of nickel is 90 mol % or more, based on 100 mol % of the metal content in the positive electrode active material.
[0019] According to one embodiment of the present invention, a positive active material is provided, which includes a layered metal oxide crystal structure of a lithium layer and a metal layer, the crystal structure includes a first metal layer, wherein a portion of the metal in the metal layer is replaced by lithium, the crystal structure includes a first lithium layer, wherein a portion of the lithium in the lithium layer is replaced by metal, and the amount of lithium replaced in the first metal layer is greater than the amount of metal replaced in the first lithium layer.
[0020] According to one embodiment of the present invention, a method for preparing a positive active material is provided. The method satisfies the following mathematical formula 1. The method comprises: preparing a metal hydroxide precursor and a lithium raw material; mixing and calcining the metal hydroxide precursor and the lithium raw material; the calcination temperature is t, the molar ratio of lithium in the lithium raw material to the metal in the metal oxide precursor is l / m; the t is below 780°C,
[0021]
Mathematical formula 1
[0022] 500≤t / (l / m)≤710
[0023] Specifically, 530≤t / (l / m)≤710, or 600≤t / (l / m)≤710.
[0024] Effects of the Invention
[0025] According to one embodiment of the present invention, a positive electrode active material and a lithium secondary battery including the same achieve high price competitiveness, high stability, high energy density, high capacity, and long life characteristics. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 , a schematic diagram showing the chemical structure of a lithium-excess high-nickel positive electrode active material.
[0027] Figure 2 , represents the X-ray diffraction pattern of the positive electrode active material of the comparative example.
[0028] Figure 3 , represents the X-ray diffraction pattern of the positive electrode active material of the example.
[0029] Figure 4 , represents the X-ray diffraction pattern of the positive electrode active material of the example.
[0030] Figure 5 , a graph showing the contents of Li2CO3 and Li2O remaining in the positive electrode active material of the comparative example.
[0031] Figure 6 , a diagram showing the contents of Li2CO3 and Li2O remaining in the positive electrode active material of the example.
[0032] Figure 7 , a diagram showing the contents of Li2CO3 and Li2O remaining in the positive electrode active material of the example.
[0033] Figure 8 , is a graph showing an analysis of the nickel oxidation number of the positive electrode active material of the comparative example.
[0034] Fig. 9 , is a graph showing an analysis of the nickel oxidation number of the positive electrode active material of the example.
[0035] Fig.10 , is a graph showing an analysis of the nickel oxidation number of the positive electrode active material of the example.
[0036] Fig.11 , which is a graph showing an analysis of the lithium content in the positive electrode active material structure of the example and the comparative example.
[0037] Fig.12 , which is a graph showing an analysis of positive ion mixing in the positive electrode active materials of the examples and comparative examples.
[0038] Fig.13 , a graph showing the electrochemical characteristics of a battery of a comparative example.
[0039] Fig.14, a diagram showing the electrochemical characteristics of a battery according to an embodiment.
[0040] Fig.15 , a diagram showing the electrochemical characteristics of a battery according to an embodiment.
[0041] Fig.16 , is a graph showing the life characteristics of a battery of a comparative example.
[0042] Fig.17 , a graph showing the life characteristics of a battery according to an embodiment.
[0043] Fig.18 , a graph showing the life characteristics of a battery according to an embodiment.
[0044] Fig.19 , which is a pairing distribution function (PDF) analysis diagram of the positive electrode active material prepared in the comparative example.
[0045] Fig. 20 , which is a pairing distribution function (PDF) analysis diagram of the positive electrode active materials prepared in the examples and comparative examples. DETAILED DESCRIPTION
[0046] Hereinafter, embodiments of the present invention will be described in detail; however, the present invention can be implemented in various different ways and is not limited to the embodiments described herein.
[0047] According to one embodiment of the present invention, a positive electrode active material is provided. The positive electrode active material comprises a layered metal oxide crystal structure of a lithium layer and a metal layer, wherein the crystal structure comprises a first metal layer, wherein a portion of the metal in the metal layer is replaced by lithium, wherein the crystal structure comprises a first lithium layer, wherein a portion of the lithium in the lithium layer is replaced by metal, wherein the amount of lithium replaced in the first metal layer is 1.5 mol% or more, and the content of nickel is 80 mol% or more, based on the metal content in the positive electrode active material being 100 mol%.
[0048] The positive electrode active material may be a layered positive electrode active material in which a transition metal layer and a lithium layer are repeatedly present.
[0049] At this time, cation exchange can occur by appropriate control, and some lithium in the lithium layer can be mixed into the transition metal layer, and conversely, on the other hand, the metal in the transition metal layer can be mixed into the lithium layer.
[0050] At this time, a representative metal of the transition metal layer may be nickel.
[0051] The replacement amount of lithium in the first metal layer may be 1.5 mol % to 15 mol %.
[0052] More specifically, it may be 4.7 mol% to 15 mol%. Alternatively, it may be 6.2 mol% or more, 7.0 mol% or more, 10.7 mol% or more. If this range is satisfied, improved life characteristics may be obtained.
[0053] The amount of metal replaced in the first lithium layer may range from 0.5 mol% to 5 mol%. That is, the amount of metal replaced may be less than the amount of lithium replaced. More specifically, it may be less than 4.7 mol% or less than 3.3 mol%.
[0054] The replacement amount of lithium in the first metal layer may differ from the replacement amount of metal in the first lithium layer by 1 mol % to 15 mol %.
[0055] According to one embodiment of the present invention, the lithium secondary battery active material is a high nickel-based positive electrode active material containing an excess of lithium in a compound. It is represented by the following chemical formula 1:
[0056]
Chemical formula 1
[0057] Li 1+a (Ni b M 1 1-b ) 1-a O2
[0058] In the chemical formula 1, 0 <a≤0.3,0.8<b<1,M 1 It is one or more elements selected from Co, Mn, Al, Mg, Ca, Ti, V, Cr, Zr, Nb, Mo, and W. (More specifically, 0 <a<0.2)
[0059] Here, excess lithium means that excess lithium enters the structure of the active material and lithium occupies some transition metal sites. Figure 1 As shown, a chemical structure diagram of a positive electrode active material according to an embodiment of the present invention shows a structure containing excess lithium at Ni, Co and / or Mn transition metal sites. According to an embodiment of the present invention, the molar content of lithium present in the structure of the positive electrode active material is 1.02 to 1.15 relative to 1 mol of the positive electrode active material.
[0060] For example, the molar content of lithium can be measured by neutron diffraction analysis. The molar content of lithium present in the positive active material structure can be expressed as 1.02 to 1.30 per mole of the compound represented by the chemical formula 1. In the chemical formula 1, the range of a representing the lithium content in the active material structure in (1+a) can be, for example, 0.005≤a≤0.19, 0.01≤a≤0.17 or 0.02≤a≤0.15.
[0061] In addition, the high nickel system means that the nickel content in the active material is high, specifically, it can mean that the nickel content can be greater than 80 mol% based on the total content of transition metals excluding lithium. For example, the nickel content can be greater than 81 mol%, 85 mol%, 89 mol%, 90 mol% or at least 92 mol%.
[0062] In the chemical formula 1, the b value representing the nickel content may be 0.81≤b≤0.99, 0.83≤b≤0.99, 0.85≤b≤0.99, 0.87≤b≤0.99, 0.89≤b≤0.99, 0.90≤b≤0.99, 0.91≤b≤0.99, 0.92≤b≤0.99 or 0.81≤b≤0.98.
[0063] The positive electrode active material according to an embodiment of the present invention is a high nickel-based material with a nickel content exceeding 80 mol %, and the lithium doping content in the active material is 1.02 mol to 1.15 mol, which is an active material containing excess lithium.
[0064] Generally speaking, although high nickel-based positive electrode active materials have achieved high capacity, their synthesis itself is difficult and their structural stability is difficult to ensure. Moreover, even if they are synthesized, Ni 2+ The cation mixing phenomenon of ions occupying lithium sites will also increase, resulting in frequent capacity reduction and difficulty in ensuring battery safety. When excessive lithium raw materials are added during the synthesis process to reduce cation mixing and increase capacity, lithium often does not enter the active material structure and remains in the form of impurities such as Li2CO3 or Li2O, which will reduce the capacity of the battery and cause stability problems.
[0065] Therefore, the inventors found that the electrochemical performance of the high nickel-based positive active material with excessive lithium changes significantly due to slight changes in the lithium composition and changes in the synthesis temperature, and can be synthesized at a specific temperature within a specific lithium content range, when the nickel content is very high and a certain amount of lithium is added to the active material structure, when charging and discharging in the range of 2.5V to 4.25V, the c-axis lattice constant change rate of the R-3m structure is less than 2.3% stable structure, and a positive active material with a stable structure is successfully prepared. The positive active material synthesized at the same time achieves high capacity and high energy density, while improving the life characteristics and stability of the battery.
[0066] According to an embodiment of the present invention, the lithium-excess high nickel-based positive active material has a c-axis lattice constant change rate of less than 2.3% when charged and discharged in the range of 2.5V to 4.25V. Specifically, the lithium secondary battery of the positive active material performs real-time X-ray diffraction pattern analysis when charged and discharged in the range of 2.5V to 4.25V, and analyzes the resulting change in lattice constant. Accordingly, the positive active material according to an embodiment of the present invention has a very small change in X-ray diffraction peak. The a-axis lattice parameter and the c-axis lattice parameter change little, and the change rate of the c-axis lattice constant meets 2.5% or less. Therefore, it can be understood that due to the presence of lithium in the transition metal layer, the phase change is suppressed and the change in lattice constant is reduced. When the lattice constant change rate meets the above range, the strain and cracks in the positive active material during charge and discharge are suppressed, and the cracks or shedding of the positive active material are reduced, which improves the life characteristics of lithium and significantly improves the lithium secondary battery.
[0067] The positive active material can be expressed as having a c-axis lattice constant change rate of 2.5% or less in the layered structure of the compound represented by Chemical Formula 1 when charged and discharged in the range of 2.5V to 4.25V, measured by real-time X-ray diffraction analysis. Alternatively, a lithium secondary battery containing a positive active material can be expressed as having a c-axis lattice constant change rate of 2.5% or less in the layered structure of the compound represented by Chemical Formula 1 when charged and discharged in the range of 2.5V to 4.25V, measured by real-time X-ray diffraction analysis.
[0068] In addition, the c-axis lattice constant may be a value measured using the R-3m structure model, or may be a value measured using the C2 / m structure model. Alternatively, it may be a value measured using a mixed model of the R-3m structure and the C2 / m structure. Regardless of which structure model is measured, the rate of change of the c-axis lattice constant due to charge and discharge can be satisfied to be less than 2.5%.
[0069] The rate of change of the c-axis lattice constant of the positive electrode active material due to charge and discharge can be, for example, less than 2.2%, less than 2.0%, less than 1.8%, less than 1.7%, less than 1.5%. It can also be less than 1.0%, more than 0.1%, more than 0.2%, more than 0.3%, more than 0.4%, more than 0.5%. The structure of the positive electrode active material that meets the above range is very stable and will not collapse or break even after repeated charge and discharge. Therefore, it can show excellent life characteristics and achieve high capacity.
[0070] Here, the c-axis lattice constant of the positive electrode active material can be derived by the calculation formula {(MAX-MIN) / MAXx100} according to the change rate (%) of charging and discharging. In the calculation formula, when the positive electrode active material is charged and discharged in the range of 2.5V to 4.25V, MAX represents the maximum value of the c-axis lattice, and MIN represents the minimum value of the c-axis lattice.
[0071] In addition, when charged and discharged in the range of 2.5V to 4.25V, the minimum value of the c-axis lattice constant of the positive electrode active material can be 99.5% or more, for example, 99.6% or more, 99.7% or more, 99.8% or more, 99.9% or more compared to the initial lattice constant. In this case, the positive electrode active material can maintain structural stability even after repeated charge and discharge, and thus can exhibit excellent life characteristics.
[0072] The positive electrode active material may have a c-axis lattice constant of an R-3m structure when charged and discharged in the range of 2.5V to 4.25V. to range, for example, it can be to to to to When the c-axis lattice constant varies within this narrow range, the positive electrode active material can achieve structural stability even after repeated charge and discharge, and thus can exhibit long life characteristics.
[0073] In addition, when charging and discharging in the range of 2.5 V to 4.25 V, the minimum value of the c-axis lattice constant of the positive electrode active material can be 99.5% or more, for example, 99.6% or more, 99.7% or more, 99.8% or more, or 99.9% or more compared to the initial lattice constant. In this case, the positive electrode active material can maintain structural stability even after repeated charge and discharge, and thus can exhibit excellent life characteristics.
[0074] The positive electrode active material may have a c-axis lattice constant of an R-3m structure when charged and discharged in the range of 2.5V to 4.25V. to The range varies, for example, to to to to When the c-axis lattice constant varies within this narrow range, the positive electrode active material can achieve structural stability even after repeated charge and discharge, and thus can exhibit high life characteristics.
[0075] Here, the change in the c-axis lattice constant can refer not only to the value during the initial charge and discharge, but also to the value of the second and third repeated charge and discharge. Therefore, the positive active material structure according to one embodiment of the present invention is stable and can show a very low c-axis lattice constant change even after repeated charge and discharge.
[0076] According to the positive electrode active material of one embodiment of the present invention, the content of nickel in the lithium site, that is, the cation mixture is less than 5 atomic %. In the case of a high nickel-based positive electrode active material with a nickel content exceeding 80 mol %, due to the Ni 2+ The excessive cation mixing phenomenon of ions occupying lithium sites has the problem of reduced capacity. On the other hand, in the positive electrode active material according to one embodiment of the present invention, excess lithium occupies some transition metal sites, the average oxidation number of the transition metal increases, and the cation mixing shows a corresponding decrease. For example, it has been confirmed that excess lithium increases the average oxidation number of nickel, inhibits the formation of the rock salt phase of the Ni(II)-O bond on the surface of the positive electrode active material, and reduces cation mixing to inhibit the dissolution of nickel. The cation mixing can be, for example, less than 4.5 atomic%, less than 4.0 atomic%, less than 3.5 atomic%. When the cation mixing amount meets the above range, the positive electrode active material can obtain sufficient capacity and ensure battery stability.
[0077] Since the positive electrode active material is a material in which the excess added lithium successfully enters the active material structure, the impurity content of Li2CO3, Li2O, etc. remaining in the active material is very low. Specifically, the content of Li2CO3 present in the positive electrode active material can be less than 0.5 weight %, for example, less than 0.4 weight %. In addition, the content of Li2O present in the positive electrode active material can be less than 1.0 weight %, for example, less than 0.8 weight % or less than 0.5 weight %. The content of Li2CO3 and Li2O can be measured by X-ray diffraction analysis. If the content of impurities such as Li2CO3 and Li2O meets the above range, it proves that the positive electrode active material structure with excess lithium has been successfully synthesized, and the positive electrode active material satisfying this structure can achieve high capacity and exhibit excellent battery characteristics with high life characteristics.
[0078] According to one embodiment of the present invention, the positive electrode active material may include a compound represented by the following Chemical Formula 2.
[0079]
Chemical formula 2
[0080] Li 1+a2 (Ni b2 Mn c2 M 2 1-b2-c2 ) 1-a2 O2
[0081] In the chemical formula 2, 0 <a2<0.2,0.8<b2<1,0<c2<0.2,0≤1-b2-c2<0.2,M 2 It is one or more elements selected from Co, Al, Mg, Ca, Ti, V, Cr, Zr, Nb, Mo, and W. In the chemical formula 2, the positive electrode active material of the compound represented by can achieve high capacity and exhibit excellent battery characteristics such as long life characteristics.
[0082] According to another embodiment of the present invention, the positive active material may include a compound represented by the following Chemical Formula 3.
[0083]
Chemical formula 3
[0084] Li 1+a3 (Ni b3 Mn c3 M 3 1-b3-c3 ) 1-a3 O2
[0085] In the chemical formula 3, 0 <a3<0.2,0.8<b3<1,0<c3<0.2,0≤1-b3-c3<0.2,M 3 It is one or more elements selected from the group consisting of Mn, Al, Mg, Ca, Ti, V, Cr, Zr, Nb, Mo, and W. In the chemical formula 3, the positive electrode active material of the compound represented by can achieve high capacity and exhibit excellent battery characteristics such as long life characteristics.
[0086] According to another embodiment of the present invention, the positive active material may include a compound represented by the following Chemical Formula 4.
[0087]
Chemical formula 4
[0088] Li 1+a4 (Ni b4 Co c4 Mn d4 M 4 1-b4-c4-d4 ) 1-a4 O2
[0089] In the chemical formula 4, 0 <a4<0.2,0.8<b4<1,0<c4<0.1,0<d4<0.1,0≤1-b3-c3-d4<0.1,M 4 It is one or more elements selected from Al, Mg, Ca, Ti, V, Cr, Zr, Nb, Mo, and W. In the chemical formula 4, the positive electrode active material of the compound represented by can achieve high capacity and exhibit excellent battery characteristics such as long life characteristics.
[0090] The average particle size of the positive electrode active material is 2 μm to 25 μm, for example, 5 μm to 25 μm, 10 μm to 25 μm, 10 μm to 20 μm. When the average particle size of the positive electrode active material meets the above range, a positive electrode active material with high tap density and high unit volume energy density can be achieved.
[0091] According to one embodiment of the present invention, a method for manufacturing a positive electrode active material is provided.
[0092] More specifically, a method for manufacturing a positive electrode active material includes: a preparation step of a metal hydroxide precursor and a lithium raw material; a step of mixing the metal hydroxide precursor and the lithium raw material and sintering them at a sintering temperature of t; the molar ratio of lithium in the lithium raw material to the metal in the metal oxide precursor is l / m, t is below 780°C, and can satisfy the following mathematical formula 1.
[0093]
Mathematical formula 1
[0094] 500≤t / (l / m)≤710
[0095] Specifically, it may be 530≤t / (l / m)≤710, or 600≤t / (l / m)≤710.
[0096] If this range is satisfied, an appropriate mixing effect of metal and lithium in the positive electrode material can be obtained, thereby obtaining a positive electrode active material with improved life characteristics.
[0097] According to one embodiment of the present invention, a method for manufacturing a positive electrode active material is provided, which includes: mixing a compound precursor shown in the following chemical formula 5 with a lithium raw material in a molar ratio of 1:1.06 to 1:1.3, and performing a heat treatment step at a temperature range of 650°C to 780°C.
[0098]
Chemical formula 5
[0099] Ni b11 M 11 1-b11 (OH)2
[0100] In the chemical formula 11, 0.8 <b11<1,M 11 yes Co, Mn, Al, Mg, Ca, Ti, V, Cr, Zr, Nb, Mo, W More than one element in .
[0101] According to one embodiment of the present invention, the method for manufacturing positive electrode active materials provided can successfully synthesize high-nickel materials with a nickel content exceeding 80%, layered positive electrode active materials with excess lithium entering the structure, and can also synthesize positive electrode active materials whose c-axis lattice constant varies by less than 2.5%. The synthesized positive electrode active materials can achieve high capacity and high energy density while exhibiting excellent battery characteristics such as long life characteristics.
[0102] In the chemical formula 5, the compound represented is a transition metal hydroxide containing nickel, which is a precursor of the positive electrode active material. In the chemical formula 11, b11 represents the molar content of nickel in the total content of the transition metal, for example, 0.81≤b11≤0.99, 0.83≤b11≤0.99, 0.85≤b11≤0.99, 0.87≤b11≤0.99, 0.89≤b11≤0.99, 0.90≤b11≤0.99, 0.91≤b11≤0.99, 0.92≤b11≤0.99, 0.81≤b11≤0.98.
[0103] When synthesizing a high-nickel cathode active material with excess lithium, even a slight change in the added lithium content will affect the success or failure of the synthesis, and the electrochemical properties of the synthesized active material will also change greatly. According to one embodiment of the present invention, the mixing molar ratio of the transition metal hydroxide precursor and the lithium raw material is 1:1.06 to 1:1.3. And heat treatment is performed in a temperature range of 680°C to 780°C, and a high-capacity lithium-excess high-nickel cathode active material can be successfully synthesized while maintaining a stable structure. The mixing molar ratio of the transition metal hydroxide precursor and the lithium raw material is 1:1.06 to 1:1.25 or 1:1.06 to 1:1.2. In addition, the heat treatment temperature can be 680°C to 750°C, 680°C to 740°C, 680°C to 730°C, 680°C to 710°C, 680°C to 700°C, 690°C to 780°C or 700°C to 750°C. If the mixing ratio of the transition metal hydroxide precursor and the lithium raw material meets the above range, and the heat treatment temperature meets the above range, the target lithium-excess high nickel-based positive electrode active material can be successfully synthesized. That is, as a material with a nickel content exceeding 80 mol%, a lithium-excess positive electrode active material with a lithium molar content of 1.02 to 1.15 in the structure can be successfully synthesized. The synthesized positive electrode active material can achieve high capacity and high energy density while exhibiting excellent battery characteristics such as long life characteristics.
[0104] The transition metal hydroxide, i.e., the precursor of the positive electrode active material, can be manufactured by a conventional coprecipitation method. For example, the precursor can be a metal salt aqueous solution containing a nickel raw material such as a nickel salt, an ammonia aqueous solution as a chelating agent, and an alkaline aqueous solution such as NaOH for adjusting pH, which are put into a coprecipitation reactor, and in order to prevent oxidation of metal ions, N2 can be injected at the same time for coprecipitation reaction to manufacture.
[0105] The nickel salt may be nickel sulfate, nickel nitrate, nickel chloride, nickel fluoride or a combination thereof. The aqueous metal salt solution may further contain cobalt salts, manganese salts, aluminum salts, etc. in addition to the nickel salt. The cobalt salt may be, for example, cobalt sulfate, cobalt nitrate, cobalt chloride, cobalt fluoride or a combination thereof. The manganese salt may be, for example, manganese sulfate, manganese nitrate, manganese chloride, manganese fluoride, or a combination thereof, and the aluminum salt may be, for example, aluminum sulfate, aluminum nitrate, aluminum chloride, aluminum fluoride, or a combination thereof.
[0106] The lithium raw material may include, for example, Li2CO3, LiOH, or a combination thereof.
[0107] According to another embodiment of the present invention, there is provided a positive electrode including the positive electrode active material; a negative electrode; and a lithium secondary battery containing a non-aqueous electrolyte.
[0108] The positive electrode includes a collector and a positive electrode active material layer on the collector. The positive electrode active material layer contains a positive electrode active material, and the positive electrode active material may include the positive electrode active material for lithium secondary battery in another embodiment described above. In the positive electrode active material layer, the content of the positive electrode active material may be 90% to 99% by weight relative to the total weight of the positive electrode active material layer.
[0109] The positive electrode active material layer may further include a binder and / or a conductive material. In this case, the contents of the binder and the conductive material are 1 wt % to 5 wt % respectively relative to the total weight of the positive electrode active material layer.
[0110] The function of the binder is to make the positive electrode active material particles adhere well to each other and to make the positive electrode active material adhere well to the current collector. Typical examples of binders include: polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride; carboxylated polyvinyl chloride, polyvinyl fluoride; polymers containing ethylene oxide, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylate styrene rubber, epoxy resin, nylon, etc. These can be used, but are not limited to them.
[0111] The conductive material is used to give the electrode conductivity. For the battery, any electronic conductive material that does not cause chemical changes can be used. Examples of conductive materials include carbonaceous materials such as natural graphite, artificial graphite, carbon black, acetylene black, ketjen black, and carbon fiber; metal materials such as metal powders or metal fibers such as copper, nickel, aluminum, and silver; conductive polymers such as polystyrene derivatives; or conductive materials containing mixtures thereof.
[0112] The positive electrode current collector may include aluminum foil, nickel foil or a combination thereof, but is not limited thereto.
[0113] The negative electrode includes a current collector and a negative electrode active material layer formed on the current collector, and the negative electrode active material layer contains a negative electrode active material.
[0114] The negative electrode active material includes a material that can reversibly intercalate / deintercalate lithium ions, lithium metal, an alloy of lithium metal, a material that can conduct and deconduct lithium, or a transition metal oxide.
[0115] Since the material that can reversibly intercalate / deintercalate the lithium ions is a carbon material, any one of the carbon-based negative electrode active materials commonly used in lithium ion secondary batteries can be used. Representative examples thereof are crystalline carbon, amorphous carbon, or they can be used together.
[0116] The lithium metal alloy can use a metal alloy selected from the combinations composed of lithium and Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, and Sn.
[0117] The lithium-intercalatable and deintercalatable materials include Si, SiO x (0 < x < 2), Si-Y alloy (where Y is an element selected from the combinations composed of alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, transition metals, rare earth elements, and their combinations, excluding Si), Sn, SnO2, Sn-Y (where Y is an element selected from the combinations composed of alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, transition metals, rare earth elements, and their combinations, excluding Sn), etc.
[0118] The transition metal oxides include vanadium oxides, lithium vanadium oxides, etc. The negative electrode active material layer further contains a binder and may selectively further contain a conductive material.
[0119] The function of the binder is to make the negative electrode active material particles adhere to each other and make the negative electrode active material adhere well to the current collector.
[0120] The conductive material is used to impart conductivity to the electrode, and for the composed battery, any electronic conductive material that will not cause a chemical change can be used.
[0121] The current collector can be selected from copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate with a conductive metal coating, and their combinations.
[0122] The negative electrode and the positive electrode are prepared by mixing an active material, a conductive material and a binder in a solvent to prepare an active material composition, and applying the composition to the entire current collector. This electrode manufacturing method is well known in the art, so a detailed description is omitted herein. The above-mentioned solvent may use N-methylpyrrolidone or the like, but is not limited thereto.
[0123] The electrolyte includes a non-aqueous organic solvent and a lithium salt.
[0124] The non-aqueous organic solvent functions as a medium through which ions participating in the electrochemical reaction of the battery can move.
[0125] The lithium salt is dissolved in an organic solvent and serves as a source of lithium ions in the battery, enabling the basic lithium secondary battery to work and promoting the movement of lithium ions between the positive and negative electrodes.
[0126] Depending on the type of lithium secondary battery, there may be a separator between the positive and negative electrodes. These separators can be polyethylene, polypropylene, polytetrafluoroethylene or two or more layers thereof, or mixed multilayer films such as polyethylene / polypropylene two-layer separators, polyethylene / polypropylene / polyethylene three-layer separators, and polypropylene / polyethylene / polypropylene three-layer separators.
[0127] Lithium secondary batteries can be divided into lithium ion batteries, lithium ion polymer batteries and lithium polymer batteries according to the types of separators and electrolytes used. According to the shape, they can be divided into cylindrical, angular, coin-shaped, cosmetic bag-shaped, etc., and according to the size, they can be divided into block and film. The structure and manufacturing method of these batteries are well known in the field, so detailed description is omitted.
[0128] Hereinafter, the present invention is described in more detail by examples and comparative examples. However, these examples and comparative examples are only intended to illustrate the present invention, and the present invention is not limited to the examples and comparative examples described herein, and the present invention is only limited by the scope of the following claims.
[0129] Example
[0130] (1) Preparation of positive electrode active material precursor
[0131] Ni was produced by conventional coprecipitation method. 0.92 Co 0.04 Mn 0.04(OH)2. Specifically, NiSO4·6H2O, CoSO4·7H2O and MnSO4·H2O are dissolved in distilled water to produce a metal salt aqueous solution. After the co-precipitation reactor is prepared, N2 is injected to prevent the oxidation of metal ions during the co-precipitation reaction, and the reactor temperature is maintained at 50°C. NH4(OH) is added to the above-mentioned co-precipitation reactor as a chelating agent, and NaOH is added to adjust the pH value. The precipitate obtained by the co-precipitation process is filtered out, washed with distilled water, and dried in an oven at 100°C for 24 hours to produce a positive electrode active material precursor with an average diameter of about 14.8μm.
[0132] (2) Manufacturing of positive electrode active materials
[0133] The prepared precursor and LiOH·H2O were mixed at different molar ratios and placed in a tube furnace, and oxygen was flowed at 50 ml / min for calcination. After calcination under the conditions of Table 1 below, the product was naturally cooled to 25°C.
[0134] (3) Battery manufacturing
[0135] 92% of the manufactured positive electrode active material, 4% of the conductive material Super P, and 4% of the binder PVDF are put into the NMP solution, stirred to make a slurry, and applied to the entire aluminum collector to make the positive electrode, and then a coin half-cell with lithium metal as the negative electrode is made.
[0136]
Table 1
[0137] Molar ratio of precursor to lithium raw material Firing temperature (℃) Example 1.03 700 Example 1.06 700 Example 1.10 700 Example 1.16 700 Example 1.20 700 Example 1.30 700 Example 1.03 750 Example 1.06 750 Example 1.10 750 Example 1.16 750 Example 1.20 750 Example 1.30 750 Comparative Example 1.03 800 Comparative Example 1.06 800 Comparative Example 1.10 800 Comparative Example 1.16 800 Comparative Example 1.20 800 Comparative Example 1.30 800
[0138] Evaluation example: X-ray diffraction pattern analysis
[0139] The positive electrode active materials prepared in the examples and comparative examples were subjected to X-ray diffraction analysis, and the results are shown in Figures 2 to 4 middle. Figure 2 is the X-ray diffraction pattern of the active material in the comparative example, Figure 3 is the X-ray diffraction pattern of the active material in the example, Figure 4 This is the X-ray diffraction pattern of the active material in the examples.
[0140] exist Figures 2 to 4 In the X-ray diffraction pattern of , the broad peak near 21 degrees of the horizontal axis corresponds to the vertex on C2 / m. In the embodiment, it can be seen that as the lithium content increases, the corresponding phase in the C2 / m space group increases. Therefore, it can be indirectly confirmed that the excess lithium has penetrated into the active material. On the contrary, in the comparative example, it can be seen that even if the lithium content increases, lithium is not contained in the active material structure.
[0141] Evaluation example: Analysis of residual impurities
[0142] The contents of residual impurities Li 2 CO 3 and Li 2 O were measured by the Rietveld analysis method of X-ray diffraction analysis on the positive electrode active materials produced in the examples and comparative examples.
[0143] Said Figure 5 In the figure, the impurity content of the positive electrode active material in the comparative example is shown. Figure 6 The impurity content of the positive electrode active material in the embodiment is shown in FIG. Figure 7 The impurity content of the positive electrode active material in the examples is shown in FIG.
[0144] Said Figure 5 In the figure, it is shown that the excess lithium in the comparative example cannot enter the active material structure, but exists in the form of impurities such as Li2CO3 and Li2O. Figure 6 It is shown in the examples that the impurity content is much reduced. Figure 7 It is shown in the figure that there are almost no impurities in the example, and it can be confirmed that excess lithium has penetrated into the active material structure.
[0145] Evaluation example: Analysis of nickel oxidation water
[0146] The oxidation number of nickel was analyzed by X-ray Absorption Near-Edge Structure (XANES) analysis of the positive electrode active materials prepared in Examples 1 to 12 and Comparative Examples 1 to 6. Figure 8 The change in the oxidation number of nickel relative to the positive electrode active material in the comparative example is shown in FIG. Fig. 9 and 10 The change in the oxidation number of nickel relative to the positive electrode active material in the examples is shown in FIG.
[0147] Generally, when lithium penetrates into the active material structure and forms a lithium excess structure, lithium occupies the transition metal position and the oxidation number of the remaining transition metal increases. Figures 8 to 10 In the case of the comparative example, as the lithium content increases, the oxidation number of nickel hardly changes, but in the embodiment, it can be seen that as the lithium content increases, the oxidation number of nickel increases significantly. Therefore, it can be confirmed that the excess lithium successfully enters the active material structure and smoothly completes the synthesis of the desired positive active material.
[0148] Evaluation example: Analysis of lithium content in the structure of positive electrode active material by neutron diffraction analysis
[0149] The positive electrode active material prepared in the embodiment and comparative example of the present invention was subjected to neutron diffraction analysis using the HANARO reactor of the Korea Atomic Energy Research Institute, and was used to perform Rietveld structure refinement, thereby separating the lithium in the structure of the positive electrode active material. The content thereof was analyzed, and the results were as follows: Fig.11 shown.
[0150] See also Fig.11 It can be seen that for the active material structure in the embodiment, the molar content of lithium present in the structure of the positive electrode active material is in the range of 1.01 to 1.15 relative to 1 mol of the positive electrode active material, and it can be confirmed again that lithium enters the active material structure, which is easier than the comparative example.
[0151] Table 2 shows the analysis results of the molar concentration of lithium in the transition metal layer and the molar concentration of the transition metal in the lithium layer.
[0152] When the amount of lithium substitution in the first metal layer is 1.5 mol % or more, improved life characteristics can be obtained.
[0153] In addition, it can be confirmed that the replacement amount of lithium in the first metal layer is larger than the replacement amount of metal in the first lithium layer, and the lifespan characteristics are ensured only when the difference is 1 mol % or more.
[0154]
Table 2
[0155]
[0156] Evaluation Example 3: Neutron diffraction analysis results using Fourier transform PDF (Pair Distribution Function, distribution function) analysis
[0157] In order to understand the changes in the local structure of the MO bonds due to the substitution of excess lithium by transition metals, Fourier transformed pair distribution function (PDF) analysis of the neutron diffraction analysis results was used. Fig.19 is the PDF analysis result of the positive electrode active material prepared in the comparative example, Fig. 20 These are the PDF analysis results of the positive electrode active materials prepared in the comparative examples and embodiments.
[0158] Compare Fig.19 and Fig. 20, in the case of the comparative example synthesized at 800°C, there is no significant difference in the Ni-O bond distance. This means that regardless of the lithium / transition metal ratio added during the synthesis process, the lithium / transition metal ratio in the crystal structure remains almost constant. On the other hand, in the case of the embodiment synthesized at 700°C, as lithium becomes excessive, the Ni-O bond distance decreases. The reason for this phenomenon is that at low synthesis temperatures, the proportion of lithium in the structure increases and the proportion of transition metal decreases. As a result, the oxidation number of Ni increases and the Ni-O bond strength increases, which leads to a decrease in the Ni-O bond distance. This means that at 700°C, the structure contains excessively added lithium.
[0159] Tables 3 and 4 show data for evaluating battery characteristics according to MO length by manufacturing more diverse positive electrode materials.
[0160] It can be seen that the example in which the MO length is reduced ensures excellent life characteristics.
[0161]
Table 3
[0162] Precursor Ni Co Al Mn N86 86.5 5.5 1.0 7.0 N88 88.0 9.5 0.0 2.5 N93 94.0 5.0 1.0 1.0 N95 95.0 3.0 0.0 2.0 N97 97.0 2.0 0.0 1.0
[0163]
Table 4
[0164]
[0165] Evaluation example: Cation mixed analysis
[0166] For the positive electrode active materials prepared in Examples and Comparative Examples, the ratio of nickel in the lithium site, i.e., cation mixing, was analyzed by Rietveld analysis using neutron diffraction analysis, and the results are shown in Fig.12 See Fig.12 From the curve graph of the embodiment in, it can be seen that with the increase of lithium content and the increase of the amount of excess lithium entering the active material structure, the oxidation number of the transition metal increases and the cation mixing decreases accordingly. In addition, it can be confirmed that the cation mixing amount of the positive electrode active material of the embodiment is less than 5 atomic%. Compared with the comparative example, there is more cation mixing in the embodiment because the synthesis temperature in the embodiment is relatively lower than the temperature in the comparative example.
[0167] Evaluation example: Real-time X-ray diffraction analysis during charging and discharging
[0168] The batteries prepared in the examples and comparative examples with a molar ratio of lithium raw material to precursor of 1.30 were charged and discharged in the range of 2.5 V to 4.25 V, and the changes in the lattice constants of the R-3m structural model were analyzed by real-time X-ray diffraction analysis. X-ray diffraction analysis (XRD) was performed under a CuKα radiation The X-ray diffractometer was used (Empyrean, Malvern Panalytical).
[0169] It can be seen that the change in the lattice constant in the example is smaller than that in the comparative example. It can be seen from this that the active material prepared in the example suppresses the structural collapse or breakage caused by charging and discharging, and it can be understood that the life characteristics of the battery are improved accordingly.
[0170] The batteries manufactured in the examples and comparative examples were subjected to a second charge and discharge in the range of 2.5 V to 4.25 V, and changes in lattice constants were confirmed based on real-time X-ray diffraction analysis.
[0171] In the case of the embodiment, it can be seen that the change in the lattice constant is smaller than that of the comparative example. It can be seen that the change in the lattice constant is a reversible feature, not just a feature of the first period.
[0172] The changes in the c-axis lattice constant are specifically shown in Tables 5 and 6 below.
[0173]
Table 5
[0174]
[0175]
Table 6
[0176]
[0177] Referring to the table above, in the embodiment, the c-axis lattice constant change rate of the R-3m structure during the initial charge and discharge and the secondary charge and discharge in the range of 2.5V to 4.25V is less than 2.5%, and it can be confirmed that the maximum value of the c-axis lattice constant is less than And the change of c-axis lattice constant is less than Therefore, it can be understood that the positive electrode active material of the embodiment is very stable in structure and exhibits high life characteristics without collapse even after repeated charge and discharge. In addition, it can be seen that the change in lattice constant is controlled not only by the sintering temperature but also by the amount of lithium added.
[0178] Evaluation example: Electrochemical characteristics of batteries at high voltage
[0179] The half-cells manufactured in the examples and comparative examples were charged at a cut-off voltage of 4.9 V. The electrochemical characteristics of the battery of the comparative example are shown in FIG. Fig.13 As shown, the electrochemical characteristics of the battery of the embodiment are as follows Fig.14 The electrochemical characteristics of the battery of the embodiment are shown in Fig.15 shown.
[0180] Generally, it is known that lithium-excess materials, i.e., active materials containing excess lithium in the structure of the active material, undergo oxygen oxidation / reduction reactions at high voltages. Fig.14 and Fig.15In the case of the battery of the example shown, it was confirmed that an irreversible reaction occurred in the 4.6V subgroup at the time of the first charge, and this reaction is generally called an oxidation / reduction reaction of oxygen. Therefore, in the example, it was confirmed again that the desired lithium-excess positive electrode active material was successfully synthesized.
[0181] Evaluation example: Battery life characteristics evaluation
[0182] The batteries manufactured in Examples and Comparative Examples were charged and discharged for up to about 50 cycles to evaluate life characteristics.
[0183] The life characteristics of the battery of the comparative example are as follows Fig.16 As shown, the life characteristics of the battery of the embodiment are as follows Fig.17 and Fig.18 shown.
[0184] See also Figures 16 to 18 It can be seen that the battery of the embodiment achieves high capacity and long life characteristics.
[0185] The present invention can be implemented in various ways and is not limited to the above-mentioned embodiments. A person skilled in the art of the present invention can understand that the present invention can be implemented in other specific ways without changing the technical concept or essential features of the present invention. Therefore, it should be understood that the above-mentioned embodiments are exemplary in all aspects and are not restrictive.
Claims
1. A positive electrode active material, wherein A layered metal oxide crystal structure comprising lithium layers and metal layers, The crystal structure includes a first metal layer, wherein a portion of the metal in the metal layer is replaced by lithium, The crystal structure includes a first lithium layer, wherein a portion of the lithium in the lithium layer is replaced by a metal, The amount of lithium replacement in the first metal layer is 1.5 mol% or more, The content of nickel is 80 mol % or more, based on 100 mol % of the metal content in the positive electrode active material.
2. The positive active material according to claim 1, wherein The replacement amount of lithium in the first metal layer is 1.5 mol % to 15 mol %.
3. The positive active material according to claim 1, wherein The replacement amount of the metal in the first lithium layer is 0.5 mol % to 5 mol %.
4. The positive active material according to claim 1, wherein The amount of lithium substituted in the first metal layer is greater than the amount of metal substituted in the first lithium layer.
5. The positive active material according to claim 4, wherein The replacement amount of lithium in the first metal layer differs from the replacement amount of metal in the first lithium layer by 1 mol % to 15 mol %.
6. The positive active material according to claim 1, wherein The molar ratio of all metals in the positive electrode active material to lithium is 1.01 to 1.
2.
7. The positive active material according to claim 1, wherein When the positive electrode active material is charged and discharged in the range of 2.5V to 4.25V, the change rate of the c-axis lattice constant of the R-3m structure is 2.5% or less.
8. The positive active material for lithium secondary battery according to claim 7, When the positive electrode active material is charged and discharged in the range of 2.5V to 4.25V, the maximum value of the c-axis lattice constant of the R-3m structure is the following.
9. The positive active material for a lithium secondary battery according to claim 8, When the positive electrode active material is charged and discharged in the range of 2.5V to 4.25V, the c-axis lattice constant of the R-3m structure is to range changes.
10. The positive active material according to claim 1, wherein The bond length between the metal and oxygen in the positive electrode active material is the following.
11. The positive active material for lithium secondary battery according to claim 1, It is measured by X-ray diffraction analysis that the content of Li2CO3 present in the positive electrode active material is less than 0.5% by weight.
12. The positive active material for lithium secondary battery according to claim 1, It is measured by X-ray diffraction analysis that the content of Li2O present in the positive electrode active material is less than 1.0 wt%.
13. The positive active material for lithium secondary battery according to claims 1 to 12, The content of nickel is 90 mol % or more, based on 100 mol % of the metal content in the positive electrode active material.
14. A positive active material, wherein A layered metal oxide crystal structure comprising lithium layers and metal layers, The crystal structure includes a first metal layer, wherein a portion of the metal in the metal layer is replaced by lithium, The crystal structure includes a first lithium layer, wherein a portion of the lithium in the lithium layer is replaced by a metal, The amount of lithium substituted in the first metal layer is greater than the amount of metal substituted in the first lithium layer.
15. A method for preparing a positive active material, satisfying the following mathematical formula 1, comprising: Performing the steps of preparing a metal hydroxide precursor and a lithium raw material; as well as A step of mixing a metal hydroxide precursor with a lithium raw material and calcining the mixture; The sintering temperature is t, and the molar ratio of lithium in the lithium raw material to the metal in the metal oxide precursor is l / m; The t is below 780°C, 【Mathematical formula 1】 500≤t / (l / m)≤710.